Pengaruh Teknologi Informasi Dan Pengawasan Keuangan Terhadap Nilai Informasi Laporan Keuangan Pemerintah Daerah - Muhamad Rifandi (STIE Mandala Jember, 2018)
Usefulness of the information can be measured by it quality and it is be used in the decision making. This study aimed to analyse the factors affecting the information value of financial statements of local governments, there are the use of information technology and financial supervision area. This research used the survey method and used primary data which obtained from the population of the Head of Sub Division of Accounting in each SKPD in districts of DIY. The collection of data through questionnaires and processed using the application SmartPLS 2.0. The Results of this study indicate that the use of information technology and financial oversight of local governments significantly influence the value of the local government's financial statement information. Keywords: Value of information, information technology, financial control